Radular Morphology of Thiarid from Raja Ampat - Nur Rohmatin Isnaningsih (Masyarakat Moluska Indonesia, 2021)
Radula in gastropods is considered as a constant and conservative character that can be used in classification and phylogenetic at certain taxa level. However, character of radula is also ecophenotypic, so that the morphology of the radula can also indicates intraspecific variations that able to detect differences among species. The insights of the radular morphology specific to Thiaridae is important for classifying species within this family. Through an enzymatic procedure using the proteinase-K, five radula of Thiarid from Raja Ampat were extracted. The results of research on radula showed that the five species studied had the taeniglossan radula type. The band of the radula is 1.8 - 4.8 mm long and consists of marginal teeth, lateral teeth, and rachidian. The radula formula is 2/1/R/1/2 with a 3-4/1/3-4 rachidian pattern and a 2-3/1/2-3 lateral teeth pattern. The mesocone shape of the rachidian and lateral teeth varies between rounded and pointed.